Analisis Ekologi Keluarga terhadap Bahaya Thirdhand Smoke pada Anak - Belgis Naila Maharani; Lia Shafira Arlianty (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Smoking behavior within the family environment remains a significant public health concern, particularly due to its impact on children as a vulnerable group. While exposure to secondhand smoke has been widely studied, the risks associated with Thirdhand Smoke (THS) are still less recognized. THS refers to residual toxic substances from tobacco smoke that persist on surfaces such as furniture, clothing, and indoor environments, potentially exposing children even in the absence of active smoking (Matt et al., 2011). This study aims to analyze the dangers of thirdhand smoke exposure in children using a family ecological perspective. The research employs a qualitative approach through a literature review of recent studies related to THS and smoking behavior within family settings. The findings indicate that THS poses significant long-term health risks for children, including respiratory disorders, immune system impairment, and potential carcinogenic effects (Benowitz et al., 2009; Hang et al., 2013). The household environment is identified as the primary source of exposure, where parental smoking behavior contributes to the accumulation of toxic residues (Matt et al., 2011). In conclusion, creating a smoke-free home environment is essential to protect children from the hidden dangers of THS. Increased awareness and preventive efforts within families are crucial to reducing long-term health risks among children.